Pressure and flow control of a pulverized coal injection vessel - Birk, Wolfgang (1997)
This Master's Thesis deals with a model-based pressure and flow control of a fine coal injection vessel for use in the blast furnace injection process. Through a transportation pipe, pulverized coal is conveyed from the coal injection vessel to the blast furnace where it is injected through the tuyeres. Irregularities in the coal mass flow to the blast furnace might cause significant variations in the raw iron quality. Therefore, a control system should be in place to maintain a constant pressure in the injection vessel and a constant coal mass flow from the injection vessel to the blast furnace. By means of system modeling and identification, the structure and behavior of the coal injection vessel have been analyzed. It has been shown that by use of model-based design, the control goals can be achieved and the control performance can be sufficiently improved compared to the conventional PI- controllers. Several dynamic models of the plant have been developed. A number of control strategies are presented and compared by means of simulation studies. The LQG design method is used to design the controllers. All the controllers have been validated through experiments on the coal injection plant at SSAB Tunnplåt in Luleå, Sweden. Validerat; 20101217 (root)